Transcriptional Regulation of NUPR1 by MYH11 Activates PI3 K/AKT and Promotes Bladder Cancer Progression Through Ferroptosis and M2 Polarization of Macrophages - Lifeng Zhang DD; Li Zhang BD; Zebin Shi BD; Yuanyuan Mi DD; Lei Zhang MD; Xiaokai Shi MD; Shenglin Gao DD; Li Zuo DD (Technology in Cancer Research & Treatment)
Background NUPR1 is a small molecule protein that plays an important role in tumor progression and drug resistance. Our previous study found that NUPR1 promotes the progression of bladder cancer, but the specific mechanism is still unclear. MYH11 encodes the smooth muscle myosin heavy chain and belongs to the conventional myosin family. MYH11 has been found to be associated with a variety of malignant tumors. Methods We identified MYH11 as an upstream regulator of NUPR1 using a bioinformatics approach and tested this hypothesis by knocking down MYH11 and ChIP-qPCR. Subsequently, we verified the association of MYH11 and NUPR1 with the PI3 K/AKT pathway by WB. In addition, gene enrichment results showed that the effect of NUPR1 on bladder cancer was related to ferroptosis and M2 macrophage polarization. We examined ferroptosis metabolites in bladder cancer cells overexpressing NUPR1 and expression of the M2 macrophage marker CD206 in NUPR1 overexpression or MYH11 knockdown bladder cancer cells. Results Bioinformatics results showed that MYH11 was positively correlated with NUPR1, and there may be a mutual binding site at the promoter of NUPR1. Knockdown of MYH11 decreased NUPR1 expression, and ChIP-qPCR showed that MYH11 bound to the promoter of NUPR1. Subsequently, WB results showed that MYH11 knockdown inhibited the PI3 K/AKT pathway, whereas NUPR1 overexpression activated this pathway. After adding ferroptosis activator, the viability of bladder cancer cells decreased, and the content of Fe 2+ and MDA increased. However, ferroptosis was significantly inhibited after overexpression of NUPR1. Knockdown of MYH11 inhibited M2 macrophage polarization, while overexpression of NUPR1 promoted this process. Conclusion This study suggests that MYH11 activates the PI3 K/AKT pathway by up-regulating the expression of NUPR1, and promotes bladder cancer progression by inhibiting ferroptosis and promoting M2 polarization of macrophages.